Strength development and flexural behavior of reinforced concrete beam using one-part alkali-activated binder. (26th April 2021) - Kumar, Amit; Kumar, Virendra; Prasad, Brajkishor
Highlights: The CAB contain 85% GGBFS and 15% of powder blended chemicals. The manufactured specimens using CAB was cured in water as well as in air. The mix preparation with CAB is a single part system. The CAB behave similar to other conventional binder. The CAB specimen could cured in water as well as in ambient condition. Abstract: The paper discusses the property of a novel alkali-activated (AA) binder that only contains 85% blast furnace slag in grounded from and 15% powdered chemicals. The paper includes a comparison between the conventional binder and novel binder of different content, tested at different conditions to analyze it properly. The paper also discusses the behavior of AA and conventional binder reinforced beams. From the study, it's evident that the AA binder performs better in pure concrete case but in RC member the conventional binder outperforms the test for all the binder content.